2000
DOI: 10.2337/diabetes.49.11.1810
|View full text |Cite
|
Sign up to set email alerts
|

Testicular sertoli cells protect islet beta-cells from autoimmune destruction in NOD mice by a transforming growth factor-beta1-dependent mechanism.

Abstract: Testicular Sertoli cells protect pancreatic islet grafts from allo- and autoimmune destruction; however, the mechanism(s) of protection is unclear. The aim of this study was to determine whether Fas ligand (FasL) and/or transforming growth factor (TGF)-beta, immunoregulatory proteins produced by Sertoli cells, might mediate the protective effects of these cells against autoimmune destruction of islet beta-cells. Sertoli cells were purified from testes of NOD mice and implanted under the right renal capsule of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
112
1

Year Published

2001
2001
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 132 publications
(117 citation statements)
references
References 31 publications
(46 reference statements)
4
112
1
Order By: Relevance
“…In addition to the ability of transplanted SCs to protect themselves in immunologically foreign environments, SCs were shown to protect islets and neuronal cells from immunemediated rejection. 9,10,[14][15][16][17][18][19] The ability of SCs to protect themselves from immunemediated destruction, as well as their ability to produce a variety of proteins, has novel and potentially far-reaching implications for gene therapy. Gene therapy is an emerging field with the goal of replacing defective and deficient proteins to restore function in disease states.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to the ability of transplanted SCs to protect themselves in immunologically foreign environments, SCs were shown to protect islets and neuronal cells from immunemediated rejection. 9,10,[14][15][16][17][18][19] The ability of SCs to protect themselves from immunemediated destruction, as well as their ability to produce a variety of proteins, has novel and potentially far-reaching implications for gene therapy. Gene therapy is an emerging field with the goal of replacing defective and deficient proteins to restore function in disease states.…”
Section: Introductionmentioning
confidence: 99%
“…While the use of SCs to deliver therapeutic proteins has potential applications across numerous clinical situations, the greatest amount of data collected to date have been focused on diabetes and Parkinson's disease (PD). 9,10,[14][15][16][17][18][19] It is not our goal to review these data here; however, it seems intuitively obvious that the consistent ability to graft SCs in animal models of diabetes and PD successfully provides a strong foundation for further exploration of transgenic SCs in these same preclinical systems. For instance, islet transplantation for the treatment of type I diabetes was recently demonstrated to be a viable option.…”
Section: Introductionmentioning
confidence: 99%
“…24,25 Tissue transplantation studies confirmed that SCs provide immune protection resulting in prolonged survival of grafts after cotransplantation with SCs. 26,27 Most cells undergo apoptosis during spermatogenesis, and the cytoplasmic compartments of sperm form residual bodies that are shed before maturation. Phagocytic removal of the apoptotic germ cells and residual bodies is critical in maintaining testicular homeostasis and normal spermatogenesis.…”
Section: Immune Privilege In the Testismentioning
confidence: 99%
“…Also, TGF-b1 somatic gene therapy reduced insulitis and diabetes in cyclophosphamide-accelerated and natural course autoimmune diabetes in NOD mice and pancreatic IL-12 and IFN-g mRNA expression was lower [24]. In addition, we found that TGF-b1 production by testicular Sertoli cells is a mechanism by which these cells protect syngeneic islet grafts transplanted into diabetic NOD mice [25]. Similarly, TGF-b1 has been implicated as a mediator of the diabetes-preventive effects of isletreactive CD4 + T-cell clones [26,27].…”
Section: Discussionmentioning
confidence: 99%